2014
DOI: 10.1111/arcm.12122
|View full text |Cite
|
Sign up to set email alerts
|

MicroCT Imaging of Red fox Talus: A Non‐Invasive Approach to Evaluate Age at Death

Abstract: X-ray microCT imaging offers the possibility to study age-related changes of bone microstructure. In the present paper we analyse the talus of 15 modern red foxes of different ages, from 2 months old to adulthood, to investigate the possibility of identifying their different ages at death. Surface and volumetric variables describing bone properties are measured or evaluated from the microCT images following three approaches: (i) the bone volume to total volume ratio, quantified for the whole bones; (ii) two ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…We have shown that the structural characteristics of antler are reliable in identifying samples with a useful degree of phylogenetic precision—these two species are separated only by subfamily: Cervinae for red deer and Capreolinae for reindeer [ 68 ]. More generally, although the expression of the phenotype could be influenced by multiple endogenous (sex, age, and heredity) and exogenous (nutrition, photoperiod, accidents during development, and social relations) factors specific to each individual [ 69 – 75 ], the morphometric criteria identified in this study nonetheless appear to be promising biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the structural characteristics of antler are reliable in identifying samples with a useful degree of phylogenetic precision—these two species are separated only by subfamily: Cervinae for red deer and Capreolinae for reindeer [ 68 ]. More generally, although the expression of the phenotype could be influenced by multiple endogenous (sex, age, and heredity) and exogenous (nutrition, photoperiod, accidents during development, and social relations) factors specific to each individual [ 69 – 75 ], the morphometric criteria identified in this study nonetheless appear to be promising biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of these specimens was influenced by their availability. The fox bones (specimens 1 and 2) were analyzed in a previous study (Boschin et al 2015) and are part of the osteological reference collection of the University of Siena (specimens 160 and 149, respectively). The red fox and roe deer specimens came from adult individuals, while the domestic pig talus came from a subadult (about 1 year old).…”
Section: Methodsmentioning
confidence: 99%
“…First, since trabecular structure is related to an animal's form of locomotion (Barak et al 2001), biomechanical studies involving burned bones need to consider how burning may contribute to the observed trabecular structure. Trabecular parameters are also related to age-at-death (Boschin et al 2015) and heat-induced changes could lead to misinterpretations if the age-at-death is inferred from microscopic observations. The analysis of burned specimens belonging to different age classes would help to clarify if burned specimens can be analysed to obtain at least an approximate age-at-death.…”
Section: Research Communicationmentioning
confidence: 99%
See 2 more Smart Citations